Assessing the reliability of permanganate-oxidizable carbon as an index of soil labile carbon - Tirol-Padre, A.; Ladha, J.K. (Wiley, 2004)
Soil C oxidized by neutral KMnO4, or permanganate‐oxidizable C (POC), has been used as an index of labile C by several workers, although the nature of organic C (OC) oxidized has not been well elucidated. This study aimed to determine the reactivity of diverse organic compounds found in the soil with KMnO4 to judge the reliability of POC as an index of labile C. Sugars, amino acids, and other organic acids reacted slowly with 33 mM KMnO4 (2–45% C oxidized in 1 h), while compounds containing glycol groups (e.g., ascorbic acid and pyrogallol) were oxidized quickly by KMnO4 (25% C oxidized in 1 min). Permanganate did not oxidize cellulose, which is decomposed by soil microbial enzymes. The POC of organic manures and plant residues was positively correlated with lignin content. The rates of oxidation of SOM with KMnO4 varied among different rice (Oryza sativa L.) soils and were highly correlated with total soil C. The clay + silt/OC ratio negatively affected POC rendering physical protection for oxidizable C groups. In the soil, KMnO4 more rapidly oxidized less readily available organic compounds than the water‐soluble carbohydrates, indicating that it did not discriminate the nonlabile from labile C. Soil POC was better correlated with total C (P < 0.01) than with water‐soluble C (WSC) (P < 0.05) and was not correlated with microbial biomass C (MBC). Carbon oxidized by KMnO4 is not a reliable measure of labile C and should be referred to as POC when used as a parameter for characterizing soil C.